Unraveling the Multi-Omic Landscape of Extracellular Vesicles in Human Seminal Plasma - Laura Governini; Alesandro Haxhiu; Enxhi Shaba; Lorenza Vantaggiato; Alessia Mori; Marco Bruttini; Francesca Loria; Natasa Zarovni; Paola Piomboni; Claudia Landi; Alice Luddi (Biomolecules)
Extracellular Vesicles (EVs) from seminal plasma have achieved attention due to their potential physiopathological role in male reproductive systems. This study employed a comprehensive proteomic and transcriptomic approach to investigate the composition and molecular signatures of EVs isolated from human seminal plasma. EVs from Normozoospermic (NORMO), OligoAsthenoTeratozoospermic (OAT), and Azoospermic (AZO) subjects were isolated using a modified polymer precipitation-based protocol and characterized for size and morphology. Comprehensive proteomic analysis, using both gel-free and gel-based approaches, revealed distinct protein profiles in each group (p<0.01), highlighting potential molecules and pathways involved in sperm function and fertility. The data are available via ProteomeXchange with identifiers PXD051361 and PXD051390, respectively. Transcriptomic analysis confirmed the trend of a general downregulation of AZO and OAT compared to NORMO shedding light on regulatory mechanisms of sperm development. Bioinformatic tools were applied for functional omics analysis; the integration of proteomic and transcriptomic data provided a comprehensive understanding of the cargo content and regulatory networks present in EVs. This study contributes to elucidating the key role of EVs in the paracrine communication regulating spermatogenesis. A full understanding of these pathways not only suggests potential mechanisms regulating male fertility but also offers new insights into the development of diagnostic tools targeting male reproductive disorders.